2019
DOI: 10.1073/pnas.1912638116
|View full text |Cite
|
Sign up to set email alerts
|

Unintegrated HIV-1 DNAs are loaded with core and linker histones and transcriptionally silenced

Abstract: Upon delivery into the nucleus of the host cell, linear double-stranded retroviral DNAs are either integrated into the host genome to form the provirus or act as a target of the DNA damage response and become circularized. Little is known about the chromatinization status of the unintegrated retroviral DNAs of the human immunodeficiency virus type 1 (HIV-1). In this study, we used chromatin immunoprecipitation to investigate the nature of unintegrated HIV-1 DNAs and discovered that core histones, the histone v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
56
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(63 citation statements)
references
References 51 publications
(64 reference statements)
7
56
0
Order By: Relevance
“…We used ChIP-PCR to quantify the level of two inhibitory chromatin modifications (H3K9me3 and H3K27me3) and two activating chromatin modifications (H3K4me3 and H3Ac) on integrated and unintegrated HIV-1 DNA in the presence and absence of Tax. As previously reported (16), unintegrated HIV-1 DNA was significantly enriched for repressive H3K9 trimethylation, and depleted for activating H3K4 trimethylation, when compared to integrated proviruses ( Fig. 4A).…”
Section: Tax Expression Allows In-hiv-1 To Mount a Spreading Infectionsupporting
confidence: 86%
See 3 more Smart Citations
“…We used ChIP-PCR to quantify the level of two inhibitory chromatin modifications (H3K9me3 and H3K27me3) and two activating chromatin modifications (H3K4me3 and H3Ac) on integrated and unintegrated HIV-1 DNA in the presence and absence of Tax. As previously reported (16), unintegrated HIV-1 DNA was significantly enriched for repressive H3K9 trimethylation, and depleted for activating H3K4 trimethylation, when compared to integrated proviruses ( Fig. 4A).…”
Section: Tax Expression Allows In-hiv-1 To Mount a Spreading Infectionsupporting
confidence: 86%
“…These increases in viral DNA and protein expression were lost when a replication incompetent, env-deficient HIV-1 was analyzed, and hence must result from virus spread ( Fig. 2E and F Previously, it has been reported that unintegrated retroviral DNA is rapidly chromatinized after nuclear entry and then decorated with inhibitory epigenetic marks that are removed, by an unknown process, after integration occurs (16,17). Here, we demonstrate that Tax expression also reduces the deposition of inhibitory chromatin marks, and increases the deposition of activating marks, on unintegrated proviral DNA (Fig.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Indeed, integrated viral DNA was measured in TGCs by Alu-gag PCR and was inhibited by a RT inhibitor, demonstrating the specificity of this detection. In addition, early viral protein synthesis was observed in labelled germ cells using confocal microscopy, an indicator of viral integration since unintegrated HIV-1 DNA is associated with transcriptional silencing [65]. Finally, viral proteins detection in TGCs by flow cytometry was inhibited by both RT and integrase inhibitors.…”
Section: Discussionmentioning
confidence: 99%